2019
DOI: 10.1177/1932296819841353
|View full text |Cite
|
Sign up to set email alerts
|

System Accuracy Assessment of a Blood Glucose Meter With Wireless Internet Access Associated With Unusual Hypoglycemia Patterns in Clinical Trials

Abstract: Background: In recent randomized clinical trials, an unusual reporting pattern of glycemic data and hypoglycemic events potentially related to an internet enabled blood glucose meter (MyGlucoHealth, BGM) was observed. Therefore, this clinical study was conducted to evaluate the system accuracy of the BGM in accordance with the ISO15197:2015 guidelines with additional data collection. Methods: To investigate system accuracy, 10 of 3088 devices and 6 of 23 strip lots, used in the trials, were selected by a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…The results of the clinical study are reported in the same issue of this journal. 8 Since, the devices and test strips were stored at different trial sites, quality assurance for storage cannot be controlled. However, the similarity of results observed across the devices and strips, originating from different geographical locations, vote against the notion that this factor has driven the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the clinical study are reported in the same issue of this journal. 8 Since, the devices and test strips were stored at different trial sites, quality assurance for storage cannot be controlled. However, the similarity of results observed across the devices and strips, originating from different geographical locations, vote against the notion that this factor has driven the results.…”
Section: Discussionmentioning
confidence: 99%
“…7 Therefore, it was necessary to evaluate the accuracy of the devices and strip lots used by patients in the trials using standard laboratory tests and in a clinical study (reported in the same issue of this journal). 8…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, Pfützner and colleagues concluded that the tested BGMs did not meet the minimum accuracy criteria specified for this study. 3 Second, Demircik and colleagues concluded that the BGMs met repeatability requirements, but their studies also demonstrated a significant positive measurement bias in the low range (below mg/dL). 4 In addition, in their studies the product failed the ISO15197:2015 criteria for hematocrit interference.…”
Section: Accuracy Results In a Two-part Surveillance Studymentioning
confidence: 99%
“…The articles in this issue of JDST by first authors Philis-Tsimikas, Pfützner, and Demircik 1,3,4 demonstrated a potential safety risk to subjects volunteering for clinical trials, who used a BGMS that the three sets of authors found to be inaccurate according to the protocols that they used. While none of the three protocols was exactly the same as what is specified in the ISO and FDA standards, the three studies showed similar results and suggest that this BGMS would not perform according to these standards, if a formal postmarket test or a surveillance test were to be performed on them with methods specified by FDA or ISO.…”
Section: What Is Needed For Surveillance Of Blood Glucose Monitor Sysmentioning
confidence: 99%